PEMANFAATAN BIOGAS SEBAGAI BAHAN BAKAR GENERATOR SET MOTOR BENSIN - Ach. Kusairi S.; Kelvin Yangsen (Universitas Lambung Mangkurat, 2015)
Biogas is a compound formed from the decomposition of organic substances in anaerobic condition, the main constituent of biogas is methane and carbon dioxide, biogas can be used as fuel or otto cycle engine with diesel. In this study, the use of biogas from the landfill Cahaya Kencana then to gasoline motor generator sets using this type with a capacity 1kVA four steps that have been previously modified in order to be able to use biogas, but no purification process before being used as fuel. This study aims to determine the purification process biogas to be used as fuel biogas, conversion techniques on gasoline motor generator set in order to use biogas, gain settings on the carburetor and faucet pipes that optimum flow generator sets can be well lit, and the last to know Performance generator sets that have been modified to use biogas.The study was conducted by first making biogas purification devices and modifications to the intake manifold insulator and then test generator sets generator sets that have been modified, test levels and the CO2 content without purification, and the final Performance test generator with power loading.Purification levels of carbon dioxide in the biogas use in the activation CaCO3, then modifications made to the generator set that perforate the insulator and then embed napple ¼ inch and spliced using hoses and given tap ¼ inch, biogas purification flowed through the device then accommodated using plastic bags before being drained towards the generator set. The results of research that the levels of carbon dioxide in the biogas without purification ie 21614 ppm, and biogas through a purification process that is 9103 ppm. While opening the tap biogas for ½ the power load of zero to a light load (350W), while the full biogas faucet openings at medium load (650W) to full load ( 80% of the capacity of the generator). Keywords: biogas, carbon dioxide, modification, generator sets.